Hadis İlminde Müzâkere Yöntemi ve Değeri - (:unkn) unknown (My University, 2016)
Rivayetlerin kitaplara kaydedilmeye ve hadis ilimlerinin oluşmaya başladığı hicrî ikinci asra kadar hadislerin muhafazası, öğrenilmesi ve nakledilmesinin en temel yolu ezber ve müzâkeredir. Hadis ilminde meydana gelen gelişmelerle birlikte hadis öğrenim metotları değişmiş, müzâkere de farklı bir anlam ve boyut kazanmıştır. Müzâkere meclislerinde hadislerin senedlerine, râvilerine ve illetlerine ilişkin birçok konu muhaddisler tarafından tartışılmıştır. Muhaddisler, müzâkereye konu olan bu meseleleri dikkatle değerlendirmekle birlikte, söz konusu meclislerde hadis rivayetinin hedeflenmemesi dolayısıyla, aynı titizliği hadis rivayetinde göstermemişlerdir. Bu nedenle müzâkere meclislerinde hadis tahammülü tartışmalıdır ve müzâkere tahammül yöntemlerinden biri olarak görülmemiştir. Ancak müzâkere, mahiyeti itibariyle hadis i'tibâr yöntemlerinden biri olarak kabul edilebilir.

The method of preservation, learning and narration of hadith, was hıfz (memorising) and al-mudhakara (discussion) until the second century in which hadiths were recorded in books and sciences of hadith began to occur. With improvements in the science of hadith, the method of hadith education changed and al-mudhakara also gained a different approach. Chains, narrators and many subjects about the sicence of hadith were discussed in al-mudhakara. Hadith shaikhs evaluated these subjects rigorously, but there wasn't the same attention on hadith narration because these councils did not aim for narration. Therefore, tahammul (reception of hadith) within al-mudhakara is debated and al-mudhakara has not been accepted as a method of tahammul, but it can be seen as one of the significant method of i'tibar (consideration)
The Method of al-Mudhakara (The Discussion) and It's Value in the Science of Hadith
Keywords: Din Bilimi